Имитационная модель отражённого сигнала системы радиоакустического зондирования атмосферы - Гетьман, В. А. (My University, 2020)
The technique of developing a simulation model of the reflected signal of the radio-acoustic sounding system of the atmosphere is considered taking into account the parameters of the equipment and features of weather conditions.
Keywords: зондирование; атмосфера